Mesocellular Foam Incorporated With Copper And Iron As Catalyst For Azo Dyes Degradation - Jamalluddin, Nur Azimah (2016)
The use of supported catalysts based on iron (Fe) in conjunction with hydrogen peroxide (H₂O₂) for catalytic degradation of organic dyes is attracting much attention due to their capability in achieving high rate of degradation. However, conventional Fenton-based heterogeneous catalysts still suffer from some limitations that could prevent them to achieve excellent performance in reusability study. To address the drawbacks of current types of heterogeneous Fenton-based catalyst, Fe incorporated mesocellular foam (FeMCF) catalyst have been developed to treat azo dyes with different structures namely acid red B (ARB) and reactive black 5 (RB5). Variations in the swelling agent (TMB) dosage (TMB/P123 = 0.125, 0.5 and 0.75) and hydrochloric acid (HCl) concentration (2.5, 0.5 and 1.5 M) led to significant differences in the final properties of the support materials to directly influence the distribution of Fe. Fe-MCFC catalyst developed at TMB/P123 ratio of 0.75 and 1.5 M HCl was capable of incorporating most of the Fe within the pore structure as the window (6 nm) and cell (13 nm) size were large enough to accommodate Fe particles. FeMCF catalyst developed by incorporating Fe during the first step before the subsequent addition of silica precursor, Fe concentration of 10 wt. %, ammonium fluoride dosage of 0.023 g and calcination temperature of 450 °C gave the largest surface area (814 m²/g), pore volume (1.808), window/cell size (6/13 nm), highest Fe distribution with the presence of isolated Fe in the MCF framework and along with the pore channels that could overcome the formation of large Fe aggregates and pore blockages. All these features directly contributed to the generation of large amount of •OH radicals to consequently demonstrate 100 % decolorization and 95 % degradation efficiency of ARB while maintaining its activity with minor leaching of Fe (Fe leaching < 0.1 mg/L). The addition of Cu before Fe (Cu-FeMCF) gave the highest decolorization (100 %) and degradation efficiencies (99 %). Cu-FeMCF required a relatively lower energy (23.25 kJ/mol) than FeMCF (62.57 kJ/mol) to degrade RB5. The excellent performance of Cu-FeMCF could be due to a synergistic effect between Cu⁺, Fe²⁺ and Fe³⁺ on the surface of Cu-FeMCF as they could effectively participate in the reversible Fe³⁺ to Fe²⁺ processes, which are essential to continuously lead to the generation of sufficient •OH radicals to maintain the high catalytic activity and reusability performances for up to 7 cycles (decolorization > 95 %) in Fenton-like systems.